First-Line Treatment of _ALK_-Positive NSCLC - Hasna Bouchaab (healthbook TIMES. Oncology Hematology)
Non-small cell lung cancer (NSCLC) patients with rearrangements in the anaplastic lymphocyte kinase (_ALK_) gene are highly sensitive to ALK tyrosine kinase inhibitors (TKIs) like alectinib. Here, the case of a 77-year-old male patient with newly diagnosed metastatic _ALK_-positive NSCLC treated with alectinib has been discussed. The patient achieved a durable (>18 months) complete response and demonstrated excellent clinical tolerance to alectinib.